Content Analysis as a Tool for the Structural and Semantic Feature Research of the Individual Organizational Identity - Frolova, Olena (East European Journal of Psycholinguistics, 2015)
The article explains necessity and actuality of the organizational identity phenomenon research, which is one of the key factors of the interaction optimization in the «employer-employee» system. The author has offered to define the investigated construct as a result of cognitive-emotional process of considering yourself being a representative of some organization. That process is expressed not only through extralinguistic factors, but also through the language of a subject. With this in mind, the author shows the expediency and efficiency of psycholinguistic tools application (content analysis and projective techniques in particular) for the outlined problem research. With a help of empirical data, structural and semantic features of the construct have been studied. The integrated knowledge system about yourself (self-image), organization (image of the organization) and peculiarities of the organization`s team have been defined as the components of the organizational identity`s cognitive-reflective dimension. The elements of the affective-motivational component include a set of emotions that arise when the organization satisfies motivational needs. Among them are emotions caused by the self-assertion and recognition need (glorical); emotions, determined by the satisfaction level of the basic need in security and belonging (archetypical); emotions caused by implementation of interpersonal and business communication need (communicative). The features of the content of the conative-normative component of the employee`s identity are determined by two indicators: by the level of interiorization of the organizational goals and values (organizational mechanisms of self-regulation) and by the identification of behavior, aimed to achieve goals and to support the organization (real activity of the subject). References Anastazi, A., Urbina, S. (2002). Psihologicheskoe Testirovanie [Psychological Testing]. S.-Petersburg: Piter. Belyauskayte, R. (1994). Risunochnyie proby kak sredstvo diagnostiki razvitiya rebenka [Drawing as a Means of Child’s Development]. Detskiy Prakticheskiy Psiholog, 30–34. Burlachuk, L. (2007). Psihodiagnostika [Psychodiagnostics]. S.-Petersburg: Piter. Zasiekina, L. (2008). Fenomen tolerantnosti kriz prizmu etnichnogo diskursu [Phenomenon of tolerance through ethnic discourse]. Psykholohichni Perspektyvy, 11, 99 – 108.